CHALLENGES TO WOMEN’S LEADERSHIP AT PT KAWANUA DASA PRATAMA - Kong, Greticia; Lapian, Stanss L. H. V. J,; Gunawan, Emilia M. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
In recent years, women's working life has been marked by more sustainable labor force participation. However, research shows that despite an increase in the number of female employees in the work environment, the top position is still dominated by men. Their position in the company only occupies middle and lower manager positions, women do not have certain powers or rights in the company. There are various challenges that hinder women in leadership positions. This study aims to explore the challenges to women’s leadership at PT Kawanua Dasa Pratama and their solutions. This research was conducted using qualitative methods. The sample size of this study is 9 female leaders who work at PT Kawanua Dasa Pratama. The findings revealed that stereotypes, sexual harassment, work-life balance, and mentoring were the most frequently reported challenges by female leaders at PT Kawanua Dasa Pratama. To overcome these challenges, they need to continue developing themselves and working hard, manage time well between work and family, don't see feminine characteristics as weaknesses, and creating a mentor and disciple cycle between women. Companies also need to provide job training to employees and not tolerating sexual harassment and discrimination in the workplace. Keywords: women, leadership, challenges